A Review of Nausea and Vomiting in the Anaesthetic and Post Anaesthetic Environment. Issue 10 (October 2017) - Matthews, C
Postoperative nausea and vomiting (PONV) has long been known as a complication of anaesthesia and surgery. This paper focuses on the assessment of the risk factors related to PONV along with the strategies and interventions which can be put in place to manage the condition. The pharmacological and multi-modal treatment methods of managing the risk factors that contribute to PONV are discussed.